Shortest and Energy Efficient Routing Protocol for MANET - Lawrence, E. Edwin; Latha, R (International Journal of Computer Sciences and Engineering, 2025)
Tremendous traffic demands and emerging multimedia applications significantly increase the energy consumption of battery-powered mobile devices. In contrast with wired networks, energy consumption is an essential constraint in Mobile Adhoc Networks. Mobile devices have restricted battery lifetime and are most vulnerable to the energy constraints. Therefore, energy concerns have to be properly implemented while defining routing metrics. In this paper a Shortest and Energy Efficient Routing Protocol for MANET (SEERP) is proposed. It defines a strategy for selecting energy efficient route taking into consideration that in MANET, channel and energy capacity are scarce resources. SEERP chooses a routing path from source to destination based on the residual energy and number of hops. The traditional route request packet is altered to calculate the minimum energy of nodes